PENGARUH MODEL PEMBELAJARAN PROBLEM BASED INSTRUCTION DISERTAI METODE PICTORIAL RIDDLE TERHADAP HASIL BELAJAR DAN KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATA PELAJARAN FISIKA DI SMA - Dewa Ayu Desinta Dewi; Singgih Bektiarso; Subiki subiki (JURNAL PEMBELAJARAN FISIKA, 2017)
This study focuses on the effect of Problem Based Instruction learning model with Pictorial Riddle method. The purpose of this study is to evaluate the effect of Problem Based Instruction learning model with Pictorial Riddle method on the result of student’s learning physics subject in high school and to describe the students’ skill of critical thinking of students by using Problem Based Instruction learning with Pictorial Riddle method on physics subject in high school. The kind of this study is experiment with a modified post-test only control group design. Sample of this study was students of class XI in SMAN Arjasa. Data were collected by observation, documentation, testing, and interviews. Data were analyzed by Independent Sample T-Test with SPSS 22 and the percentage of the students’ skill of critical thinking. The results of this study showed that the average of learning results of experimental class is 78.05 and the control class is 67.05. The analysis of data used Independent Sample T-Test, learning results are obtained sig.(2-tailed) of 0.000 or 0.000 ≤ 0.05. This study can be concluded that there is significant influence of Problem Based Instruction learning model with Pictorial Riddle method on the result of student’s learning physics subject in high school. The results of the analysis of the students’ skill of critical thinking are obtained an averrage achievement of all the indicators of 64.91% with the good level of mastery.